DIETARY PROTEIN REQUIREMENT OF DAPHNIA MAGNA FOR THE IMPROVEMENT POPULATION AND NUTRITIONAL VALUE OF DAPHNIA - Kasmawijaya, Adang; Hasan, Otie Dylan Soebhakti; Zaidy, Azam Bachur (Chanos Chanos, 2023)
Daphnia magna is one of the live feeds used in aquaculture, but its availability is still limited. The population and nutritional quality of D. magna culture depend on the nutritional quality of feed where the feed source is commonly used from agricultural by-products. In contrast, pelleted feed as a source of nutrition in D. magna culture is still limited. Evaluation of commercial pelleted feeds with different protein levels and dietary protein requirements of D. magna is the focus of this research. Three treatments with different protein levels of feed with protein levels of 17.83% (P20), 32.35% (P30) and 41.98% (P40) and rice bran as control at a protein level of 8.2% (P10) with five replications for 28 days of rearing with using a completely randomized design. The average weekly population and the highest total biomass of D. magna were obtained from D. magna fed the P30 (Protein 32.35%) of 7,575 ind. tank-1. week-1 and total biomass of 290.26 g.m-3 with the feed conversion ratio of 3.85 ± 0.75 and protein efficiency ratio of 0.83 ± 0.14. The highest protein value of D. magna was obtained from D. magna fed the P30 of 3.02% ± 0.20 wet weight. The results showed that feed with a protein content of 32.35% (P30) showed the best results for cultivating D. magna. The estimated dietary protein requirement of feed for D. magna cultivation using the second polynomial regression analysis of feed protein - population and biomass is 38.8%.